HOSPITAL ADMISSIONS FOR MENTAL DISORDERS DUE TO ALCOHOL USE AND PSYCHOACTIVE SUBSTANCES: AN EVALUATION FROM 2018 TO 2023 - Lima, Andressa Bianca Reis (2024)
Brazil has the highest rates of anxiety disorders and is fifth in cases of depression, which drives individuals to use alcohol and psychoactive substances as a mechanism to alleviate mental suffering. This study aims to analyze the clinical and epidemiological landscape of dengue cases in the Southeast region of Brazil from 2014 to 2023. It is a descriptive, quantitative, and retrospective study based on data obtained from the Hospital Morbidity System (SIH) at the Department of Informatics of the Unified Health System (DATASUS). The total number of hospitalizations for mental disorders associated with the use of alcohol and psychoactive substances in Brazil between 2018 and 2023 was 435,923. The South region had the highest number of cases (n=181,455), with the state of Rio Grande do Sul accounting for over 54.69% of these hospitalizations. The age group with the highest frequency of cases was 30 to 39 years, corresponding to 26.89% (n=117,234) of the cases. The sample was predominantly composed of male individuals, accounting for 81.15% (n=353,754) of the total. The most frequent race/color in the analyzed sample was white, representing 45.88% (n=200,010) of the cases. Most of the care provided was in an emergency setting, corresponding to 84.61% of the cases. The average length of stay was 20.4 days. During the analyzed period, there were 2,472 deaths, with the majority occurring in individuals aged 50 to 59 years, representing 24.91% of the total. The study revealed a growing trend in the number of cases, particularly among the younger population, which may lead to severe chemical dependency.